Epilepsy in literature - А. Yu. Ulitin; А. V. Vasilenko; A. V. Ivanenko; S. S. Kolosov; I. А. Sokolov; S. А. Turanov; G. А. Ulitin; А. А. Vinogradova (Эпилепсия и пароксизмальные состояния)
This paper represents a unique study carried out by a team of physicians having diverse medical experience (practitioners, residents, students), who relying on own viewpoints positions came to a common understanding and began to consider epilepsy not only as a severe, chronic, and widespread brain disease, but also as a part of human culture reflected in many literary works. Our study was aimed at searching and analyzing available sources that describe a course of epilepsy and its impact on life of famous people as well as its role in society. Literary images created in diverse centuries and eras by writers who personally suffered from epilepsy (F.M. Dostoevsky, Edgar Allan Poe, Wilkie Collins, and many others) turned out to be so colorful and convincing that they sometimes anticipated appearance of the first descriptions in professional medical literature, and even lay down in their basis.